The Customer Citizenship Behaviors of Food Blog Users - Chen, Kaung-Hwa; Hsieh, Kuo-Jung; Chang, Feng-Hsiang; Chen, Nai-Chia (Sustainability, 2015)
Compared with previous studies that have focused on customers’ behavioral intentions or the factors that influence purchase behaviors on blogs or discussion boards, in this study, we examine the factors of independent food blogs or discussion boards that influence users’ customer citizenship behaviors. Six food blogs were selected based on the flow rate and food diaries. 323 Subjects were chosen from the blog user population and then interviewed to develop the data needed for this study. The results indicate that psychological needs, customer satisfaction, and customer-company identification positively affect customer citizenship behaviors. High satisfaction of customer-orientation is a critical management strategy on food blogs. This study adapts physically existing organizational behavior theory through appropriate inference and modification for virtual community. Unlike past studies that focused on customer purchase intention, this study emphasizes customer value and social media of the virtual community.